Heretic or Traitor? Spinoza’s Excommunication and the Challenge That Judaism Poses to the Study of Religious Diversity - Cooper, Julie E. (Political theology, 2020)
When political theorists talk about “religious diversity,” they usually intend the multiplicity of “religions” in a given society. Yet we now know that the secular, liberal framing of the problematic presupposes a controversial definition of “religion.” My primary goal, in this paper, is to reorient scholarly discussion around what we might call “the critical religion conception of diversity” - not the multiplicity of “religions,” but the myriad ways that the sacred intersects with national and political identity, some of which resist assimilation to the “religious” paradigm. Toward this end, I relate a story about Spinoza’s Hebrew reception in the interwar period. For Zionist intellectuals, Spinoza symbolized the deformations that “religion” imposed on Judaism’s self-understanding and the constraints that it placed on Jewish intellectual horizons. Studying the Zionist critique of “religion” exposes the limitations of received theoretical frameworks, which cannot address the kinds of diversity that were politically consequential for twentieth-century Jews.